Kolaborasi dan Intervensi: Pengembangan dan Operasional Maskapai Penerbangan Komersial Hindia Belanda, 1928–1940-an - Dwi Adi Wicaksono; Abdul Wahid (Universitas Gadjah Mada, 2021)
Civil aviation in the Dutch East Indies developed after the presence of Koninklijke Nederlandsch-Indische Luchtvaart Maatschappij (KNILM) as the only commercial airline. Even though KNILM was founded and owned entirely by the private sector and operated commercially, this company received subsidies and various other support from the colonial government. This raises the question of how the two parties manage this airline?This article uses a political and business approach to explain these issues as well as sources in the form of official printed documents, newspapers and others.The author's research shows that the formation and management of the KNILM company was a combination of private interests and colonial government politics. This cooperation was carried out to overcome the shortcomings of each party that requires civil aviation to strengthen their agenda. The private sector has the advantage of being able to utilize aviation technology directly with better economic value but required an injection of funds for its operations. On the other hand, the colonial government did not want to invest heavily in aviation technology but needed it, so it provided subsidies and other support to KNILM.